Structural Characteristics of Rice Bran Insoluble Dietary Fiber Bound Phenolic and Its Effect on Gut Microbiota - Yumeng SHI; Fuqiang LIANG; Ruilin GUO; Shanshan DUAN; Xinran PU; Jiayi SHI (Shipin gongye ke-ji, 2023)
Rice bran is a major source of phenolic substances in cereals, in which phenolics mainly bound with dietary fiber in the form of conjugated state. In this study, rice bran insoluble dietary fiber-bound phenolic (IDF-BP) was prepared by sequential enzymatic method. The structure of IDF-BP was characterized by confocal laser scanning microscope (CLSM), Fourier transform infrared spectrometer (FT-IR), scanning electron microscope (SEM) and X-ray diffraction. The IDF-BP was subjected to simulated gastrointestinal digestion and colon fermentation in vitro, followed by 16S rRNA high-throughput sequencing of short-chain fatty acids. The results showed that the yield of rice bran IDF-BP was 23.73%±0.008%, the content of BP was 6.11±0.085 mg GAE/g DW, and the content of ferulic acid was the highest (1.41±0.013 mg/g DW). The IDF-BP was a typical cellulose crystal form of cellulose, which had both cellulose and hemicellulose characteristic groups and ester bond characteristic peaks, indicating that bound phenolic were bound to dietary fiber in the form of ester bond. The results of intestinal flora diversity and flora abundance showed that IDF-BP could regulate the balance of intestinal flora by reducing the diversity of intestinal flora, down-regulating intestinal harmful bacteria such as Bacteroides and Phascolarctobacterium, and increase intestinal beneficial bacteria such as Bifidobacterium and Akkermansia to achieve the goal of regulating the balance of gut microbiota. Additionally, it also had the ability to boost the production of short chain fatty acids (mainly acetic acid, propionic acid and butyric acid) to adjust intestinal pH. Rice bran IDF-BP had both the characteristics of dietary fiber and phenolics, and the two had a good synergistic effect on intestinal flora and short chain fatty acids, which would indicate that rice bran IDF-BP has the potential to improve the intestinal environment, thus achieving health benefits.